Entre o presencial e o virtual: movimentos em direção a novos saberes da docência superior - Barbiero, Danilo Ribas (2013)
This study, conducted in the context of the Research Line Training, Knowledge and Professional Development, the Graduate Program in Education at Universidade Federal de Santa Maria (UFSM) aims at investigating the impact of experiences of Presencial Teaching and Virtual Teaching in the training of the university teacher. The specific objectives of the research are: to analyze the significant experiences narrated by professors of Presencial Teaching and Virtual Teaching and possible influences on their (trans) formation; understand the strategic markers present in Teaching Choreography and their transformation/reconstruction for Classroom Teaching to Virtual Teaching and vice versa and identify the possible interrelationships between Teaching Choreographies submitted in the Presencial Teaching in the Virtual Teaching from the experiences narrated. Regarding the theoretical review, we discuss fields of studies, themes and theories such as Teacher Education, the Teaching Choreography in Teaching in Higher Education, Digital Technologies of Information and Communication, Virtual Environments for Teaching and Learning, Theory History-Cultural including Activity Theory and Study Activity. In this research with qualitative approach and narrative feature, we seek the information through narrative interviews with professors of the Department of Documentation (UFSM), who teach the course Archivology (UFSM) and Postgraduate Course-Specialization of Distance Learning-Management in Archives (UAB/UFSM). The information were analyzed through discursive textual analysis. Among the search results, highlight the influences of Virtual Teaching on the Presencial Teaching, the (re) construction of teacher knowledgein the preparation of Teaching Choreographies and the role of distance tutors and monitors the training of teachers.